Ferric alginate composite charcoal gel bead catalyst as well as preparation method and application thereof

The iron alginate composite biochar gel bead catalyst, prepared from coffee grounds and sodium alginate, addresses the limitations of traditional catalysts by providing efficient, stable, and recyclable antibiotic removal in wastewater treatment.

CN119186644APending Publication Date: 2024-12-27TG HILYTE ENVIRONMENTAL TECHNOLOGY (BEIJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411321102.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional catalysts for removing antibiotic residues in water are costly, unstable, difficult to recycle, and pose secondary pollution risks, while biochar's mechanical weaknesses and aggregation limit its application in water treatment.

Method used

A method to prepare an iron alginate composite biochar gel bead catalyst using coffee grounds as a raw material, cross-linked with sodium alginate and iron ions, forming a stable, recyclable, and efficient Fenton-like catalyst.

Benefits of technology

The catalyst exhibits high catalytic activity, stability, and ease of recycling, effectively removing antibiotics from wastewater with reduced environmental impact and cost, expanding biochar's application scope.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186644A_ABST
    Figure CN119186644A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of environmental treatment, in particular to an iron alginate composite charcoal gel bead catalyst as well as a preparation method and application thereof. The preparation method of the iron alginate composite biochar gel bead catalyst comprises the following steps: a) cleaning coffee grounds of a coffee shop with deionized water and absolute ethyl alcohol for multiple times, and putting the cleaned coffee grounds into an air dry oven to obtain pretreated coffee grounds; b) under a limited oxygen condition, placing the pretreated coffee grounds in a dry crucible, and placing the dry crucible in a muffle furnace at a temperature of 850-950 DEG C for pyrolysis to obtain biochar; c) mixing the heated sodium alginate aqueous solution with the charcoal to form a mixture solution; and d) dropwise adding the mixture solution into a ferric salt solution, obtaining cross-linked gel beads through an aging process, and storing the cross-linked gel beads in a refrigerator. The iron alginate composite charcoal gel bead catalyst provided by the invention not only has good oxytetracycline hydrochloride removal capacity, but also has the characteristics of being easy to recover and realizing resource utilization of waste coffee grounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental governance and relates to an iron alginate composite biochar gel bead catalyst and a preparation method and application thereof. Background Art

[0002] With the widespread use of antibiotics, especially in the fields of medical treatment, livestock and poultry breeding, and agricultural planting, the problem of antibiotic residues in the environment is becoming increasingly serious. These residues not only pollute water bodies, but also lead to the emergence of drug-resistant strains and drug-resistant genes, posing a serious threat to human health. However, traditional physical and biological treatment methods are difficult to effectively remove organic wastes such as antibiotics. Therefore, the development of efficient removal technology has become an urgent problem to be solved.

[0003] Advanced oxidation processes (AOPs) have attracted much attention due to their ability to utilize active free radicals to remove refractory organic pollutants. 2+ Catalytic decomposition of hydrogen peroxide to generate hydroxyl radicals has been widely used. However, this method has problems such as excessive iron ions, pH restriction and the generation of a large amount of iron sludge, which limits its practical application. To solve these problems, the heterogeneous Fenton technology came into being, which generates active oxygen species through surface reactions of solid-phase catalysts to remove pollutants. Although many studies have explored new catalytic materials, there are common problems such as high catalyst cost, poor stability and the possibility of secondary pollution.

[0004] In recent years, biochar has been considered as an ideal catalyst carrier due to its low cost, green environmental protection and good metal loading capacity. Studies have shown that biochar can not only promote the reduction of high-valent metals, but also provide stable reaction sites. However, the weak mechanical properties and easy aggregation of biochar limit its application in water treatment. Therefore, it is particularly important to develop a new type of Fenton-like catalyst that is efficient, stable, economical and environmentally friendly to overcome the problem that traditional powdered catalysts are difficult to recycle and have high losses. This will not only further expand the application scope of biochar in the environmental field, but also provide a sustainable and effective solution for removing antibiotic pollutants in wastewater. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to overcome the shortcomings of existing powdered catalysts and provide a preparation method and application of an iron alginate composite biochar gel bead catalyst for water treatment. The catalyst provided by the present invention not only has good organic pollutant removal ability, but also has the characteristics of easy recycling and resource utilization of waste coffee grounds.

[0006] The present invention provides a method for preparing an iron alginate composite biochar gel bead catalyst, comprising the following steps:

[0007] a) After washing the coffee grounds with deionized water and anhydrous ethanol for multiple times, the coffee grounds are placed in an air drying oven to obtain pretreated coffee grounds.

[0008] b) placing the pretreated coffee grounds in a dry crucible under oxygen-limited conditions and placing the crucible in a muffle furnace at a temperature range of 850 to 950° C. to perform pyrolysis to obtain biochar;

[0009] c) mixing the heated sodium alginate aqueous solution with biochar to form a mixture solution;

[0010] d) dropping the mixture solution into an iron salt solution, obtaining cross-linked gel beads through an aging process, and storing the beads in a refrigerator;

[0011] Preferably, in step a), the temperature of the blast drying oven is set at 50-70° C., and the drying time is 36-72 hours; and the coffee grounds are 200-50 mesh coffee grounds.

[0012] Preferably, in step b), the operation method of the oxygen-limited condition is to use tin foil to seal and wrap the material to be heat-treated;

[0013] The heating rate of the pyrolysis is 3 to 6°C / min;

[0014] The total time of the pyrolysis is 4.5 to 6.5 hours.

[0015] Preferably, in step c), the concentration of the sodium alginate aqueous solution is 0.01-0.03 g / mL; the reaction is carried out under stirring conditions, the stirring speed is 200-400 rpm, the stirring time is 3-5 h, and the stirring temperature is 50-70° C.;

[0016] Preferably, the mass ratio of sodium alginate to biochar material is 1-3:4-6;

[0017] Preferably, in step d), the iron salt solution comprises ferrous chloride tetrahydrate and ferric chloride hexahydrate, and the molar ratio of the added ferrous chloride is 0.5-1.5:1-3;

[0018] The mass ratio of sodium alginate to iron salt is 1-4:7-11;

[0019] The mass concentration of the iron salt solution is 7-11 g: 80-120 mL;

[0020] The aging time is 16 to 22 hours, and the aging temperature is room temperature;

[0021] After the aging, rinsing is also included;

[0022] The present invention provides an iron alginate composite biochar gel bead catalyst, which is prepared according to the preparation method described in the above technical scheme.

[0023] As a technical solution concept, the present invention provides an application of the above-mentioned iron alginate composite biochar gel bead catalyst in treating organic pollutant wastewater, comprising the following steps:

[0024] A) weighing a predetermined amount of alginate iron composite biochar gel bead catalyst and hydrogen peroxide (H2O2) solution and adding them to the pollutant solution to obtain a mixed solution;

[0025] B) subjecting the mixed liquid to a degradation reaction in a shaking device;

[0026] C) performing solid-liquid separation on the water obtained in step B) to obtain treated water.

[0027] Preferably, the concentration of hydrogen peroxide is 0.05 to 22 mM;

[0028] Preferably, the added mass of the iron alginate composite biochar gel bead catalyst is 0.005 g to 0.12 g;

[0029] Preferably, the pollutant in the pollutant solution is an antibiotic, the antibiotic is oxytetracycline hydrochloride, the concentration of oxytetracycline hydrochloride is 20-40 mg / L; the volume of oxytetracycline hydrochloride solution is 80-150 mL;

[0030] Preferably, the shaking device is a constant temperature air bath shaker, the shaker temperature is 20-30°C, the shaker speed is 150-250rpm, and the degradation time is 0.5-1.5h;

[0031] Preferably, the pore size of the filter used for solid-liquid separation is 30 to 120 μm;

[0032] The iron alginate composite biochar gel bead catalyst described in the above technical solution is combined with hydrogen peroxide to oxidatively degrade and remove oxytetracycline in water.

[0033] Compared with the prior art, the advantages of the present invention are:

[0034] The invention provides a method for preparing an alginate iron composite biochar gel bead catalyst, comprising the following steps: a) washing coffee grounds from a coffee shop with deionized water and anhydrous ethanol for multiple times, and then placing the coffee grounds in a blast drying oven to obtain pretreated coffee grounds. b) placing the pretreated coffee grounds in a drying crucible under oxygen-limited conditions, and placing the pretreated coffee grounds in a muffle furnace within a temperature range of 850 to 950° C. for pyrolysis to obtain biochar; c) mixing a heated sodium alginate aqueous solution with the biochar to form a mixture solution; d) dropping the mixture solution into an iron salt solution, obtaining cross-linked gel beads through an aging process, and storing the cross-linked gel beads in a refrigerator. The invention uses coffee grounds, a domestic waste, as a biochar raw material, and uses sodium alginate to cross-link iron elements in situ to prepare a low-cost, green and environmentally friendly alginate iron composite biochar gel bead catalyst. It exhibits excellent Fenton-like catalytic activity, which is due to the doping of biochar and the cross-linking of iron ions, providing more active sites. At the same time, sodium alginate provides a stable support structure and a favorable reaction environment, further improving the mass transfer rate. Compared with traditional powdered catalysts, the beaded catalyst developed in this application overcomes the problems of difficult recycling and high loss, expands the application scope of biochar in environmental engineering, and has good adaptability and feasibility of industrial application. This provides a sustainable and effective solution for the removal of pollutants such as antibiotics in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the iron alginate composite biochar gel bead catalyst provided in Example 1 of the present invention;

[0036] Figure 2 A diagram showing the removal effect of oxytetracycline hydrochloride by the iron alginate composite biochar gel bead catalyst provided in Example 2 of the present invention at different dosages;

[0037] Figure 3 A diagram showing the removal effect of oxytetracycline hydrochloride on H2O2 at different concentrations activated by the iron alginate composite biochar gel bead catalyst provided in Example 3 of the present invention;

[0038] Figure 4 This is a diagram showing the removal effect of oxytetracycline hydrochloride under different pH conditions using the iron alginate composite biochar gel bead catalyst activated H2O2 provided in Example 4 of the present invention;

[0039] Figure 5 This is a diagram showing the removal effect of oxytetracycline hydrochloride on H2O2 activated by the iron alginate composite biochar gel bead catalyst provided in Example 5 of the present invention during storage time. DETAILED DESCRIPTION

[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0041] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0042] The present invention provides a method for preparing an iron alginate composite biochar gel bead catalyst, comprising the following steps:

[0043] a) washing the coffee grounds with deionized water and anhydrous ethanol for multiple times, and then placing the coffee grounds in an air drying oven to obtain pretreated coffee grounds;

[0044] b) placing the pretreated coffee grounds in a dry crucible under oxygen-limited conditions and placing the crucible in a muffle furnace at a temperature range of 850 to 950° C. to perform pyrolysis to obtain biochar;

[0045] c) mixing the heated sodium alginate aqueous solution with biochar to form a mixture solution;

[0046] d) dropping the mixture solution into an iron salt solution, obtaining cross-linked gel beads through an aging process, and storing the beads in a refrigerator.

[0047] In step a):

[0048] The coffee grounds were washed with deionized water and anhydrous ethanol for multiple times and then placed in a forced air drying oven to obtain pretreated coffee grounds.

[0049] In some embodiments of the present invention, the temperature of the blast drying oven is set at 50-70° C., specifically 60° C. The drying time is 36-72 hours, specifically 48 hours. The coffee grounds are 200-50 mesh coffee grounds, specifically 100 mesh coffee grounds.

[0050] In step b):

[0051] Under oxygen-limited conditions, the pretreated coffee grounds were placed in a dry crucible and placed in a muffle furnace for pyrolysis at a temperature range of 850 to 950° C. to obtain biochar.

[0052] In certain embodiments of the present invention, the oxygen-limited condition is operated by using tin foil to seal and wrap the material to be heat-treated. The pyrolysis temperature of the pretreated coffee grounds is 850-950°C, specifically 900°C. The heating rate of the pyrolysis is 3-6°C / min, specifically 5°C / min. The total time of the pyrolysis is 4.5-6.5h, specifically 5h.

[0053] In step c):

[0054] The heated sodium alginate aqueous solution is mixed with the biochar to form a mixture solution.

[0055] In certain embodiments of the present invention, the concentration of the sodium alginate aqueous solution is 0.01-0.03 g / mL, specifically 0.02 g / mL. The reaction is carried out under stirring conditions, and the stirring speed is 200-400 rpm, specifically 300 rpm. The stirring time is 3-5 h, specifically 4 h. The stirring temperature is 50-70° C., specifically 65° C.

[0056] In certain embodiments of the present invention, the mass ratio of sodium alginate to biochar material is 1-3:4-6; specifically 2:5.

[0057] In step d):

[0058] The mixture solution is dropped into an iron salt solution, and cross-linked gel beads are obtained through an aging process and stored in a refrigerator.

[0059] In certain embodiments of the present invention, the specific step of dripping the mixture solution into the iron salt solution comprises: adding the mixture solution dropwise into the iron salt solution at a fixed height using a syringe or a peristaltic pump.

[0060] In certain embodiments of the present invention, the iron salt solution includes ferrous chloride tetrahydrate and ferric chloride hexahydrate, and the molar ratio of addition is 0.5-1.5:1-3; specifically 1:2.

[0061] In certain embodiments of the present invention, the mass ratio of sodium alginate to iron salt is 1-4:7-11; specifically 2:9.

[0062] In certain embodiments of the present invention, the mass concentration of the iron salt solution is 7-11 g:80-120 mL; specifically 9:100 mL.

[0063] In certain embodiments of the present invention, the aging time is 16 to 22 hours, specifically 18 hours. The aging temperature is room temperature. After the aging, rinsing is also performed. The rinsing is performed several times using anhydrous ethanol and deionized water.

[0064] In certain embodiments of the present invention, the storage in a refrigerator includes: storing in a sealed sample bottle and storing in a refrigerator (4° C.).

[0065] The iron alginate composite biochar gel bead catalyst was obtained.

[0066] The present invention also provides a method for removing oxytetracycline hydrochloride in water, comprising the following steps:

[0067] A) weighing a predetermined amount of iron alginate composite biochar gel bead catalyst and hydrogen peroxide solution and adding them to the pollutant solution to obtain a mixed liquid;

[0068] B) subjecting the mixed liquid to a degradation reaction in a shaking device;

[0069] C) performing solid-liquid separation on the water obtained in step B) to obtain treated water.

[0070] In step A):

[0071] A predetermined amount of iron alginate composite biochar gel bead catalyst and hydrogen peroxide solution are weighed and added into the pollutant solution to obtain a mixed solution.

[0072] In certain embodiments of the present invention, the concentration of hydrogen peroxide is 0.05-22mM; specifically 0.1mM, 1mM, 5mM, 10mM, 20mM. The added mass is 0.005g-0.12g; specifically 0.01g, 0.03g, 0.5g, 0.7g, 1.0g. The pollutant in the pollutant solution is an antibiotic, and the antibiotic is oxytetracycline hydrochloride, and the concentration of oxytetracycline hydrochloride is 20-40mg / L; specifically 30mg / L. The pH of the oxytetracycline hydrochloride solution is 3-9; specifically 4.5. The volume of the oxytetracycline hydrochloride solution is 80-150mL; specifically 100mL.

[0073] In step B):

[0074] The mixed liquid is subjected to degradation reaction in a shaking device.

[0075] In certain embodiments of the present invention, the shaking device is a constant temperature air bath shaker, the shaker temperature is 20-30° C., specifically 25° C. The shaker speed is 150-250 rpm, specifically 200 rpm. The degradation time is 0.5-1.5 h, specifically 1 h.

[0076] In step C):

[0077] The pore size of the filter used for solid-liquid separation is 30-120 μm, specifically 50 μm.

[0078] In certain embodiments of the present invention, before mixing the pollutant solution with the iron alginate composite biochar gel bead catalyst and H2O2, the process further includes: adjusting the pH value of the pollutant solution to 3-6, specifically 4.5. The reagent used to adjust the pH value of the water to be treated is hydrochloric acid or sodium hydroxide.

[0079] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0080] Beneficial effects:

[0081] (1) The present invention uses coffee grounds, a domestic waste, as the raw material of biochar, and uses sodium alginate to in-situ cross-link iron elements to prepare a low-cost, green and environmentally friendly alginate-iron composite biochar gel bead catalyst. The catalyst uses the rich carbon source and porous structure of coffee grounds and the good gelling property of sodium alginate to effectively introduce iron ions into the biochar matrix, forming a catalyst with high specific surface area and good dispersibility.

[0082] (2) The iron alginate composite biochar gel bead catalyst prepared by the present invention exhibits excellent Fenton-like catalytic activity, which is mainly attributed to its unique material structure and composition. First, the doping of biochar provides the material with rich pore structure and active sites, increasing the surface area and reaction rate of the catalytic reaction. Secondly, the cross-linking effect of iron ions further enhances the oxidation ability of the catalyst and significantly improves its degradation efficiency of pollutants. In addition, sodium alginate, as a matrix material, not only provides a stable support structure, which greatly improves the stability of the catalyst in water, but also creates a favorable reaction environment, effectively promoting the mass transfer process.

[0083] (3) Compared with traditional powdered catalysts, the iron alginate composite biochar gel bead catalyst prepared by the present invention overcomes the problems of powdered catalysts being difficult to recycle, easy to lose, and having a short service life. Because its particles are large and have good mechanical strength, they can be easily separated and recycled in practical applications, reducing the loss of the catalyst and the risk of secondary pollution to the environment.

[0084] (4) The iron alginate composite biochar gel bead catalyst prepared by the present invention is simple and easy to operate, low in cost, suitable for large-scale production, and has good adaptability and feasibility of industrial application. It expands the application scope of biochar in the environmental field and has good adaptability and feasibility of industrial application. This provides a sustainable and effective solution for the removal of pollutants such as antibiotics in wastewater.

[0085] In order to further illustrate the present invention, the preparation method and application of an iron alginate composite biochar gel bead catalyst provided by the present invention are described in detail below in combination with examples, but it should not be understood as limiting the scope of protection of the present invention.

[0086] Example 1

[0087] This embodiment provides an iron alginate composite biochar gel bead catalyst, and the preparation method thereof comprises the following steps:

[0088] 1. The coffee grounds from the coffee shop were washed with deionized water and anhydrous ethanol for multiple times, and then placed in a forced air drying oven at 60°C for 48 hours to obtain pretreated coffee grounds.

[0089] 2. Under oxygen-limited conditions, the pretreated coffee grounds were placed in a muffle furnace and pyrolyzed at 900°C (heating rate of 5°C / min) for 3 h to obtain biochar for later use.

[0090] 3. Dissolve 2g of sodium alginate in 100mL of deionized water, heat to 65°C and stir continuously until it is completely dissolved and bubbles are eliminated. Then add 5g of dry 100-mesh coffee grounds and continue stirring until completely mixed to obtain a mixture solution;

[0091] 4. The mixture solution is loaded into a syringe and added dropwise into 100 mL of an iron salt mixed solution from a fixed height (the iron salt solution includes 7.033 g (26 mmol) of ferric chloride hexahydrate and 2.584 g (13 mmol) of ferrous chloride tetrahydrate; the solvent in the iron salt solution is deionized water). The obtained cross-linked gel beads are aged at room temperature for 18 h, and then rinsed with deionized water to obtain an iron alginate composite biochar gel bead catalyst, which is stored in a refrigerator (4°C).

[0092] The scanning electron microscope (SEM) image of the prepared iron alginate composite biochar gel bead catalyst is shown in Figure 1 As shown, Figure 1 The SEM image of the iron alginate composite biochar gel bead catalyst provided in Example 1 of the present invention. It can be observed that the surface of the iron alginate composite biochar gel bead catalyst has a three-dimensional lamella morphology, and the addition of biochar makes it have a convex structure, which not only provides sufficient space for the attachment of pollutants and the occurrence of Fenton-like reactions, but also enhances the expansion performance of the gel beads. At the same time, the interlayer structure formed inside the iron alginate composite biochar gel bead catalyst can also be observed, which is conducive to the diffusion and circulation of water inside and outside, thereby improving its catalytic efficiency for H2O2.

[0093] Example 2

[0094] To further investigate the effect of the dosage of the iron alginate composite biochar gel bead catalyst prepared in Example 1 on the activation of H2O2 to remove oxytetracycline hydrochloride. 100mL of oxytetracycline hydrochloride solution was added to a 250mL conical flask, the concentration of the oxytetracycline hydrochloride solution was 30mg / L, and the pH value was 4.5; then, 0.01, 0.03, 0.05, 0.07, and 0.10g of the iron alginate composite biochar gel bead catalyst and 5mM of H2O2 were weighed and added to the conical flask in sequence; the conical flask was placed in a constant temperature air bath shaker, the temperature was set to 25°C, the speed was set to 200rpm, and the time was 60min; at fixed time points (2, 5, 10, 15, 30, 45, 60min), a pipette was used to collect an appropriate amount of the mixture solution, and the oxytetracycline hydrochloride concentration of different solution samples was immediately determined at 354nm using a UV-visible spectrophotometer.

[0095] The oxytetracycline hydrochloride treatment results are as follows Figure 2 As shown, Figure 2 The removal effect diagram of oxytetracycline hydrochloride by the alginate iron composite biochar gel bead catalyst provided in Example 2 of the present invention at different dosages. It can be found that with the increase of the dosage of the alginate iron composite biochar gel bead catalyst (0.1-0.5g / L), the removal rate of oxytetracycline hydrochloride in 60min shows a significant increase trend, rising from 78.13% to 91.31%. When the dosage continues to increase, the removal rate increases slowly, and when the concentration is 1g / L, it is only increased to 94.40%. This phenomenon may be because the hydrogel beads have a unique reactive lamellar channel structure, which can not only improve the mass transfer rate, but also control the reaction process, so that the removal of oxytetracycline hydrochloride can be carried out under high reaction rate conditions. Considering the pollutant removal efficiency and economic cost, when the alginate iron composite biochar gel bead catalyst dosage is 0.5g / L, the catalytic oxidation system shows the highest cost performance.

[0096] Example 3

[0097] Based on the above experiment, the effect of H2O2 solution concentration on the removal efficiency of oxytetracycline hydrochloride was further investigated. 100 mL of oxytetracycline hydrochloride pollutant solution was added to a 250 mL conical flask, the concentration of oxytetracycline hydrochloride solution was 30 mg / L, and the pH value was 4.5; 0.05 g of alginate iron composite biochar gel bead catalyst and H2O2 were weighed and added to the conical flask in sequence, where the H2O2 concentrations were 0.1, 1.0, 5.0, 10.0, and 20.0 mM, respectively; the conical flask was placed in a constant temperature air bath shaker, the temperature was set to 25 ° C, the speed was set to 200 rpm, and the time was 60 min; at fixed time points (2, 5, 10, 15, 30, 45, 60 min), a pipette was used to collect an appropriate amount of the mixture solution, and the oxytetracycline hydrochloride concentration of different solution samples was immediately measured at 354 nm using a UV-visible spectrophotometer.

[0098] The oxytetracycline hydrochloride treatment results are as follows Figure 3 As shown, Figure 3The removal effect diagram of oxytetracycline hydrochloride by activating different concentrations of H2O2 with the alginate iron composite biochar gel bead catalyst provided in Example 3 of the present invention. It can be found that in the alginate iron composite biochar gel bead catalyst / H2O2 system, as the H2O2 concentration increases from 0.1 to 5mM, the removal rate of oxytetracycline hydrochloride increases from 49.76% to 91.31%, reaching a maximum value. When the concentration continues to increase to 20mM, the removal rate drops to 87.44%. This is because when the H2O2 concentration has not yet reached saturation, a reasonable increase in the H2O2 concentration can produce more free radicals such as ·OH during the reaction process and be fully and effectively utilized. When the H2O2 concentration exceeds the saturation value, a large amount of ·OH will be produced in the system in a short time, and ·OH mutual quenching will occur, thereby reducing the removal rate of oxytetracycline hydrochloride. Therefore, in order to ensure the pollutant removal effect, 5mM is subsequently selected as the optimal dose of H2O2.

[0099] Example 4

[0100] Based on the above experiment, the effect of pH on the degradation of oxytetracycline hydrochloride by catalyst activation of H2O2 was further investigated. 100 mL of oxytetracycline hydrochloride pollutant solution was added to a 250 mL conical flask, and the concentration of oxytetracycline hydrochloride solution was 30 mg / L; the solution pH was adjusted to 3.0, 4.5, 5.0, 7.0, and 9.0 respectively; 0.05 g of alginate iron composite biochar gel bead catalyst and 5 mM H2O2 were weighed and added to the conical flask in sequence; the conical flask was placed in a constant temperature air bath shaker, the temperature was set to 25 ° C, the speed was set to 200 rpm, and the time was 60 min; at fixed time points (2, 5, 10, 15, 30, 45, 60 min), a pipette was used to collect an appropriate amount of the mixture solution, and the concentration of oxytetracycline hydrochloride of different solution samples was immediately measured at 354 nm using a UV-visible spectrophotometer.

[0101] The oxytetracycline hydrochloride treatment results are as follows Figure 4 As shown, Figure 4The removal effect of oxytetracycline hydrochloride under different pH conditions by activating H2O2 with alginate iron composite biochar gel bead catalyst provided in Example 4 of the present invention is shown. It can be observed that pH 4.5 is the optimal reaction condition for the alginate iron composite biochar gel bead catalyst / H2O2 system, and the removal rate of oxytetracycline hydrochloride is 91.31%. When pH = 3.0, the removal rate is slightly reduced to 88.54%. This phenomenon may be due to the fact that acidic conditions are not conducive to the formation of Fe(II), thereby inhibiting the cyclic reaction between Fe(II) / Fe(III). When the pH is further increased to neutral, the removal rate of oxytetracycline hydrochloride is 89.56%, indicating that the catalytic oxidation system can maintain good Fenton-like catalytic performance under neutral conditions. As the pH value continues to increase, the reduction in removal effect may be attributed to the following two points: (1) H2O2 tends to decompose to generate O2 and H2O under alkaline conditions, and the number of hydroxyl radicals generated is reduced. (2) The active iron ions on the surface of the material are prone to generate iron hydroxide and other complexes under alkaline conditions, which hinder the activity of the material and lead to a decrease in catalytic efficiency. The above results prove that the iron alginate composite biochar gel bead catalyst composite material can effectively degrade oxytetracycline hydrochloride in a wide pH range, showing good practical application potential.

[0102] Example 5

[0103] Based on the above experiments, we further investigated whether the catalyst performance could achieve long-term stability. 100 mL of oxytetracycline hydrochloride pollutant solution was added to a 250 mL conical flask, the concentration of oxytetracycline hydrochloride solution was 30 mg / L, and the pH value was 4.5; the iron alginate composite biochar gel bead catalyst and H2O2 were weighed and added to the conical flask in turn, the specific amounts were 0.025 g&2.5 mM, 0.05 g&5.0 mM, and 0.15 g&15.0 mM, respectively; the storage time of the iron alginate composite biochar gel bead catalyst was 1 day, 30 days, 60 days, and 180 days, respectively; the above-mentioned conical flask was placed in a constant temperature air bath shaker, the temperature was set to 25 ° C, the speed was set to 200 rpm, and the time was 60 min; at fixed time points (2, 5, 10, 15, 30, 45, 60 min), a pipette was used to collect an appropriate amount of the mixture solution, and the oxytetracycline hydrochloride concentration of different solution samples was immediately determined using a UV-visible spectrophotometer (at 354 nm).

[0104] The oxytetracycline hydrochloride treatment results are as follows Figure 5 As shown, Figure 5The removal effect diagram of oxytetracycline hydrochloride by activating H2O2 with the iron alginate composite biochar gel bead catalyst provided in Example 5 of the present invention at different storage times. It can be seen from the results that under the conditions of the three dosage combinations, a relatively stable oxytetracycline hydrochloride removal rate can be maintained at each time stage. Especially after 180 days of sealed storage, the removal of oxytetracycline hydrochloride by the iron alginate composite biochar gel bead catalyst / H2O2 (0.5g / L&5mM) can still reach more than 90%, which is almost the same as the freshly prepared material. This shows that the catalytic activity of the iron alginate composite biochar gel bead catalyst is not limited by the storage time, and long-term stability can be achieved without additional storage means. This also proves that the catalyst material prepared by a simple cross-linking method can meet the large-scale production in subsequent practical applications.

Claims

1. The present invention provides a method for preparing an iron alginate composite biochar gel bead catalyst, comprising the following steps: a) washing the coffee grounds with deionized water and anhydrous ethanol for multiple times, and then placing the coffee grounds in an air drying oven to obtain pretreated coffee grounds; b) placing the pretreated coffee grounds in a dry crucible under oxygen-limited conditions and placing the crucible in a muffle furnace at a temperature range of 850 to 950° C. to perform pyrolysis to obtain biochar; c) mixing the heated sodium alginate aqueous solution with biochar to form a mixture solution; d) dropping the mixture solution into an iron salt solution, obtaining cross-linked gel beads through an aging process, and storing the beads in a refrigerator.

2. The preparation method according to claim 1, characterized in that: In step a), the temperature of the blast drying oven is set at 50-70° C.; the drying time is 36-72 hours; and the coffee grounds are 200-50 mesh coffee grounds.

3. The preparation method according to claim 1, characterized in that: In step b), the operation method of the oxygen-limited condition is to use tin foil to seal and wrap the material to be heat-treated; the pyrolysis temperature of the pretreated coffee grounds is 850-950° C.; the heating rate of the pyrolysis is 3-6° C. / min; and the total pyrolysis time is 4.5-6.5 h.

4. The preparation method according to claim 1, characterized in that: In step c), the concentration of the sodium alginate aqueous solution is 0.01-0.03 g / mL; the mixing reaction is carried out under stirring conditions; the stirring speed is 200-400 rpm; the stirring time is 3-5 hours; the stirring temperature is 50-70° C.; The mass ratio of the sodium alginate to the biochar material is 1-3:4-6.

5. The preparation method according to claim 1, characterized in that: In step d), the specific steps of dripping the mixture solution into the iron salt solution include: adding the mixture solution dropwise into the iron salt solution at a fixed height using a syringe or a peristaltic pump; The iron salt solution includes ferrous chloride tetrahydrate and ferric chloride hexahydrate, and the molar ratio of the added ferrous chloride is 0.5-1.5:1-3; The mass ratio of sodium alginate to iron salt is 1-4:7-11; The mass concentration of the iron salt solution is 7-11 g: 80-120 mL; The aging time is 16 to 22 hours; the aging temperature is room temperature; after the aging, rinsing is also included; The storing in a refrigerator includes: storing in a sealed sample bottle.

6. The iron alginate composite biochar gel bead catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. The application of the above-mentioned iron alginate composite biochar gel bead catalyst in treating organic pollutant wastewater comprises the following steps: A) weighing a predetermined amount of iron alginate composite biochar gel bead catalyst and hydrogen peroxide solution and adding them to the pollutant solution to obtain a mixed liquid; B) subjecting the mixed liquid to a degradation reaction in a shaking device; C) performing solid-liquid separation on the water obtained in step B) to obtain treated water.

8. The use according to claim 7, characterized in that: In step A), the concentration of hydrogen peroxide is 0.05-22 mM; the added mass of the alginate iron composite biochar gel bead catalyst is 0.005 g-0.12 g; The pollutant in the pollutant solution is an antibiotic, and the antibiotic is oxytetracycline hydrochloride, and the concentration of oxytetracycline hydrochloride is 20 to 40 mg / L; the volume of the oxytetracycline hydrochloride solution is 80 to 150 mL.

9. The use according to claim 7, characterized in that: In step B), the shaking device is a constant temperature air bath shaker, the shaker temperature is 20-30° C., the shaker speed is 150-250 rpm, and the degradation time is 0.5-1.5 h.

10. The use according to claim 7, characterized in that: In step C), the pore size of the filter used for solid-liquid separation is 30 to 120 μm.